2022
DOI: 10.3889/oamjms.2022.8051
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Incidence, Rate of Thrombolytic Therapy, Mortality in Thailand from 2009 to 2021

Abstract: BACKGROUND: Thrombolytic treatment is the main treatment of acute ischemic stroke. Thailand started thrombolytic treatment in 2008 only at university hospitals in Bangkok and gradually increased services in large provincial hospitals until widespread in 2014. However, no studies regard the services in stroke management in Thailand. AIM: This study aims to present data: incidence, rate of thrombolytic treatment, mortality rate of acute stroke in Thailand for 13 years METHODS: A study from the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It should be noted that there could be regional differences which ranging from 5 to 22%. These results are supported by a Thai study using national stroke data [ 23 ] which showed that the percentage of acute ischemic stroke patients who were treated with thrombolysis varied widely across the country.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It should be noted that there could be regional differences which ranging from 5 to 22%. These results are supported by a Thai study using national stroke data [ 23 ] which showed that the percentage of acute ischemic stroke patients who were treated with thrombolysis varied widely across the country.…”
Section: Discussionsupporting
confidence: 60%
“…It seems possible that stroke service delivery was improved due to the improvement of stroke fast track and thrombolytic treatment in mid-level and standard-level referral hospitals. Thrombolysis treatment can be provided at mid-level referral hospitals by non-neurologist, such as internists or emergency physicians, under the supervision of a neurologist from advanced-level or standard-level referral hospitals [ 23 ]. It should be noted that there could be regional differences which ranging from 5 to 22%.…”
Section: Discussionmentioning
confidence: 99%
“…A survey across 44 European countries reported an average of 7.3% of thrombolysis between 2016 and 2017 whereas country-specific rates in Europe were higher in Czech Republic (23.5% in 2018) and the Netherlands (21.7% in 2016) ( Table 3 ) ( 3 ). The reported rates however, were noticeably lower in low and middle-income countries such as Thailand (7.8% in 2019) ( 19 ), Vietnam (5.6–8.5% in 2020) ( 20 ) and China (5.6% between 2019 and 2020) ( 21 ). Direct country comparison of the rates however, was not feasible owing to differences in study methods and reporting years.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2002 when Thailand endorsed Universal Health Coverage (UHC), stroke has been covered under public health, but the rate of thrombolysis use (0.18–8.04%) remains limited. 27 Bhutan also provides UHC for its citizens. However, most other countries in the SEAR do not have UHC, and therefore, despite the availability of advanced medical technology, poor affordability limits its equitable usage.…”
Section: Stroke Systems Of Care and Challenges To Stroke Services In ...mentioning
confidence: 99%